Knowledge Management and Performance in Franchise-Structured Organisation - Abdul Majid, Izaidin; Md. Saad , Mohd. Shamsuri; Yahya, A. (2010)
Franchising is fast gaining the reputation of a rapid growing and profitable industry. The nature of franchise system offers both the franchisor and franchisee a quick and cost-efficient way to operate and expand. Furthermore, the availability of different franchise structures within the franchise system provides the flexibility to cater different needs and market thus contributing to their performance. However, the ability of the franchise system to ensure an organised transfer of knowledge between the various franchise structures is crucial to achieve the targeted performance growth. Within this framework, this paper will try to articulate the synergistic relationship between franchise structures and knowledge management in Malaysian franchise system in influencing their franchise performance.